From Desiccation to Global Climate Change: A History of the Desertification Narrative in the West African Sahel, 1900-2018. (1st March 2019) - Benjaminsen, Tor A.; Hiernaux, Pierre
During the last few decades, 'desertification' has reached the status of a global environmental issue. The African Sahel is often seen as the world region worst hit by this process. The idea that deserts are spreading, mainly due to local land-use practices, is, however, not new. It already existed early in the colonial period in tropical Africa. The purpose of this paper is to provide a historical perspective on the construction of the desertification narrative using historical documents combined with a review of international scientific research. The main focus is on former French colonies in the West African Sahel, and the paper aims to identify various phases in the history of the desertification narrative in this region and to explain the shifts between these phases. We first present debates among French scientists in the early twentieth century about desiccation as a natural or human-induced process. We continue by discussing the transition from desiccation theory to a narrative focusing more explicitly on desert advance caused by local human activities. Thereafter, we show how the droughts in the Sahel of the 1970s and 1980s enhanced the desertification narrative and led to an institutionalisation of desertification at different levels, which again established this idea as a global environmental problem. Finally, we demonstrate how global climate change has further strengthened the idea of desertification as a global environmental threat, despite international scientific research questioning the scale and relevance of this perceived problem. This history of the desertification narrative from the early colonial period to today shows how the narrative has created some powerful winners, while the losers have largely been Sahelian small-scale farmers and pastoralists. This is also a case illustrating how a policy narrative may use science when science supports its main tenets, but neglects science when it turns against the narrative.